E-Beam Metallization and Optimization Using Second-Order Single Response Surface Methodology - Sapaw, Rohana; Ahmad, brahim; Zaharim, Azami; Dolah, Asban; Sahar, Siti Kudnie; Rajaee, Nordiana (Malaysian Journal of Science, 2005)
This paper presents a statistical designed experiment for equipment characterization, optimization and modeling of the e-beam evaporation on the thickness uniformity. There were two setting parameters of equipment that affect the process of metallization which are temperature and current. The effects on point-to-point and wafer-to-wafer thickness uniformity using second-order Single Response Surface Methodology (SRSM) were investigated. First-order experiment was done but the improvement in term of lack of fit was needed. Therefore, a second-order experiment of single response surface methodology with 13 runs has yield fitted model for point-to-point thickness uniformity of 97%, 98.2% and 97.5% for wafer 1,2 and 3 respectively. However the model for wafer-to-wafer thickness uniformity was not significant. The models that were significant can be used to optimize the setting parameter of e-beam evaporation.